2015
DOI: 10.1074/jbc.m114.635375
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase 1 (Plk1) Up-regulates Telomerase Activity by Affecting Human Telomerase Reverse Transcriptase (hTERT) Stability

Abstract: Background: hTERT plays a central role for telomerase activity and telomeric chromatin maintenance. Results: Plk1 interacts with hTERT and regulates its stability. Overexpression of Plk1 up-regulates the activity of telomerase. Plk1 enhances the chromatin loading of hTERT and inhibits its ubiquitination. Conclusion: Plk1 is a positive regulator of telomerase. Significance: We revealed the mechanism of Plk1 regulating the telomerase activity by stabilizing hTERT protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Huang et al reported that Plk1, while associated with an active telomerase complex, improves the loading of hTERT onto chromatin, presumably promoting its nuclear retention and inhibiting cytosolic ubiquitination. Overexpression of Plk1 leads to an increase in hTERT protein levels without affecting the mRNA levels, supporting the hypothesis that nuclear retention mediated through Plk1 prevents proteasomal degradation of hTERT and increases telomerase activity [ 162 ]. Though Plk1 is a kinase, it was not reported to phosphorylate hTERT, nor was the kinase activity of Plk1 necessary for telomerase association.…”
Section: Htert Regulationsupporting
confidence: 61%
See 1 more Smart Citation
“…Huang et al reported that Plk1, while associated with an active telomerase complex, improves the loading of hTERT onto chromatin, presumably promoting its nuclear retention and inhibiting cytosolic ubiquitination. Overexpression of Plk1 leads to an increase in hTERT protein levels without affecting the mRNA levels, supporting the hypothesis that nuclear retention mediated through Plk1 prevents proteasomal degradation of hTERT and increases telomerase activity [ 162 ]. Though Plk1 is a kinase, it was not reported to phosphorylate hTERT, nor was the kinase activity of Plk1 necessary for telomerase association.…”
Section: Htert Regulationsupporting
confidence: 61%
“…Whether this interaction regulates hTERT strictly through retention within its organelle of action, through reducing proteasomal degradation, or through a combination of both mechanisms remains to be investigated. Interestingly, the novel telomerase-associated protein Polo-like kinase 1 (Plk1) was speculated to activate telomerase through a related but opposite mechanism [ 162 ]. Huang et al reported that Plk1, while associated with an active telomerase complex, improves the loading of hTERT onto chromatin, presumably promoting its nuclear retention and inhibiting cytosolic ubiquitination.…”
Section: Htert Regulationmentioning
confidence: 99%
“…One unique DNA structure that is important to the linear chromatin maintenance is the telomere. Telomeres are repetitive DNA sequences that protect the chromosome ends from replicative degradation and erroneous recognition and ligation as DSBs [ 131 ]. Telomeres work in concert with the shelterin complex which is composed of telomeric repeat binding factor 1 and 2 (TERF1, TERF2), protection of telomeres protein 1 (POT1), TERF1 interacting nuclear factor 2 (TINF2), tripeptidyl-peptidase 1 (TPP1), and repressor activator protein 1 (RAP1) [ 132 ].…”
Section: Plk1 and Maintenance Of Dna Integritymentioning
confidence: 99%
“…In regards to this, PLK1 interacts with hTERT, and hTERT activity positively correlates with PLK1 activity, suggesting enhanced PLK1 action leads to increased telomere maintenance [ 131 ]. PLK1 inhibition results in increased telomeric fusions, suggesting a loss of the protective telomere function [ 136 ].…”
Section: Plk1 and Maintenance Of Dna Integritymentioning
confidence: 99%
See 1 more Smart Citation